MOLECULER DOCKING SENYAWA BIOAKTIF KULIT RARU (Cotylelobium melanoxylon) TERHADAP TARGET α-GLUKOSIDASE DAN α-AMILASE - Josita Jenny Haryanti Hutagulung; Roy Indrianto Bangar (Jurnal Kesehatan Farmasi, 2026)
Diabetes mellitus is a metabolic disease that affects the body’s ability to control blood glucose levels, making effective treatments necessary to reduce postprandial glucose increases. Flavonoid compounds from raru bark (Cotylelobium melanoxylon) have shown potential as inhibitors of carbohydrate-digesting enzymes, especially α-amylase and α-glucosidase. This study aimed to evaluate the antidiabetic potential of flavonoid compounds from raru bark using an in silico approach with molecular docking. Five flavonoid compounds—rutin, isoquercetin, quercetin, quercitrin, and isoquercitrin—were tested to examine their binding ability to the target enzymes. The results showed that rutin and isoquercetin had lower binding energy values than the standard ligand, indicating more stable interactions and stronger enzyme inhibition. These findings suggest that flavonoid compounds from raru bark may be developed as natural antidiabetic agents; however, further in vitro and in vivo studies are needed to confirm their safety and effectiveness.